Copy number neutral loss of heterozygosity at 17p and homozygous mutations of TP53 are associated with complex chromosomal aberrations in patients newly diagnosed with myelodysplastic syndromes - Svobodová, Karla; Zemanová, Zuzana; Lhotská, Halka; Novakova, Milena; Podskalska, Lucie; Beličková, Monika; Březinová, Jana; Šárová, Iveta; Izáková, Silvia; Lizcová, Libuše; Berková, Adéla; Šišková, Magda; et al. (Leukemia research, 2016)
Complex karyotypes are seen in approximately 20% of patients with myelodysplastic syndromes (MDS) and are associated with a high risk of transformation to acute myeloid leukemia and poor outcomes in patients. Copy number neutral loss of heterozygosity (CN-LOH, i.e., both copies of a chromosomal pair or their parts originate from one parent) might contribute to increased genomic instability in the bone-marrow cells of patients with MDS. The pathological potential of CN-LOH, which arises as a clonal aberration in a proportion of somatic cells, consists of tumor suppressor gene and oncogene homozygous mutations. The aim of our study was to evaluate the frequency of CN-LOH at 17p in bone-marrow cells of newly diagnosed MDS patients with complex chromosomal aberrations and to assess its correlation with mutations in the TP53 gene (17p13.1). CN-LOH was detected in 40 chromosomal regions in 21 (29%) of 72 patients analyzed. The changes in 27 of the 40 regions identified were sporadic. The most common finding was CN-LOH of the short arm of chromosome 17, which was detected in 13 (18%) of 72 patients. A mutational analysis confirmed the homozygous mutation of TP53 in all CN-LOH 17p patients, among which two frameshift mutations are not registered in the International Agency for Research on Cancer TP53 Database. CN-LOH 17p correlated with aggressive disease (median overall survival 4 months) and was strongly associated with a complex karyotype in the cohort studied, which might cause rapid disease progression in high-risk MDS. No other CN-LOH region previously recorded in MDS or AML patients (1p, 4q, 7q, 11q, 13q, 19q, 21q) was detected in our cohort of patients with complex karyotype examined at the diagnosis of MDS. The LOH region appeared to be balanced (i.e., with no DNA copy number change) when examined with conventional and molecular cytogenetic methods. Therefore, a microarray that detects single-nucleotide polymorphisms is an ideal method with which to identify and further characterize CN-LOH. Our data should specify the prognosis and should lead to the identification of potential targets for therapeutic interventions.
Keywords: mutace; DNA Copy Number Variations; dospělí; lidské chromozomy, pár 17; Tumor Suppressor Protein p53; Oligonucleotide Array Sequence Analysis; Female; Adult; ženské pohlaví; mutační analýza DNA; Gene Dosage; jednonukleotidový polymorfismus; High-Throughput Nucleotide Sequencing; variabilita počtu kopií segmentů DNA; lidé; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Polymorphism, Single Nucleotide; DNA Mutational Analysis; Mutation; Aged, 80 and over; Loss of Heterozygosity; Myelodysplastic Syndromes; retrospektivní studie; myelodysplastické syndromy; Male; ztráta heterozygozity; chromozomální aberace; Aged; vysoce účinné nukleotidové sekvenování; nádorový supresorový protein p53; hybridizace in situ fluorescenční; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; In Situ Hybridization, Fluorescence; genová dávka; Chromosomes, Human, Pair 17; Retrospective Studies; Middle Aged; Chromosome Aberrations; Humans